The Turbot War: Gunboat Diplomacy or Refinement of the Law of the Sea? - Keiver, Michael (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1996)
This article attempts an analysis of Canadian environmental diplomacy during the recent « turbot war ». The dispute included the Canadian arrest of a Spanish fishing vessel, the Estai, beyond the 200 mile zone. Turbot, also known as Greenland halibut, is considered a straddling fish stock because it is present both within and adjacent to the 200 mile zone. The Canadian response to the straddling stock issue involved a two-track strategy of unilateral action and multilateral negotiation. Canadian multilateral efforts included participation in the United Nations Conference on Straddling Fish Stocks and Highly Migratory Fish Stocks. This paper examines the underlying causes of the straddling stocks issue as well as the rights and obligations of coastal and high seas fishing states.